Prosedur Berperkara dalam Sistem Arbitrase: Studi perbandingan antara BANI dan BASYARNAS - Reviana Putri Fadillah; Zihan Fauziah; Sawitri Yuli Hartati S (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the procedural framework governing dispute resolution before the Indonesian National Arbitration Board (BANI) and the National Sharia Arbitration Board (BASYARNAS), focusing on how both institutions construct and implement their respective adjudication stages. The analysis highlights that BANI operates with a highly systematized set of procedural guidelines supported by detailed administrative mechanisms, offering clarity and predictability for parties involved in commercial disputes. BASYARNAS, in contrast, integrates sharia principles into its procedural model, resulting in a hybrid structure that aligns national arbitration law with substantive Islamic legal norms, particularly in matters arising from muamalah-based contractual relationships. Both systems share the objective of providing efficient, confidential, and enforceable dispute settlement processes, yet the procedural differences observed demonstrate the need for further harmonization. Strengthening standardization, enhancing transparency, and improving institutional synergy between the two models may contribute to a more coherent national arbitration landscape. The findings provide an analytical foundation for future policy development and institutional refinement within Indonesia’s arbitration system.